The Influence of Discount Vouchers and Free Shipping on the Frequency of Online Food Purchases among Students Using ShopeeFood at Universitas Negeri Jakarta - Radja Rafi Aryawira; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
The expansion of financial technology (fintech) has increased digital financial engagement among university students however, higher adoption does not necessarily indicate responsible digital financial behavior. This study investigates the effects of fintech trust and financial literacy on digital financial behavior, with fintech usage decision positioned as an intervening variable. Using a quantitative approach, data were collected from 361 students of the Faculty of Economics and Business, Universitas Negeri Jakarta, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that fintech trust and financial literacy significantly influence fintech usage decisions and directly affect digital financial behavior. Nevertheless, fintech usage decision does not significantly mediate the relationship between trust, literacy, and behavioral outcomes. These results indicate the presence of a behavioral gap, where factors that encourage fintech adoption do not automatically translate into prudent financial management practices. This study contributes to the fintech and financial behavior literature by distinguishing adoption-oriented decisions from post-adoption behavioral quality, emphasizing that trust and financial literacy primarily drive usage decisions rather than ensuring responsible digital financial behavior among young users.